Differences in Levels of Prostate Specific Antigen and Insulin-like Growth Factor 1 in GSTP1 Gene Polymorphism among Workers - Roestijawati, Nendyah; Wibowo, Yudhi; Lestari, Tri (UI Scholars Hub, 2020)
Cadmium (Cd) is classified as a carcinogen in humans (IA). In addition to causing lung cancer, the incidence of prostate cancer due to Cd exposure based on epidemiological research has also increased. This study aims to identify the GSTP1 genotypic frequency distribution and its correlation with PSA and IGF-1 levels in Cd exposed and unexposed workers. The research design used was cross sectional in 23 exposed groups (weld workers) and 40 unexposed groups (office employees) with a total of 63 people. The measurement of PSA and IGF-1 levels was carried out using the ELISA method and identification of the GSTP1 gene polymorphism using the PCR-RFLP method. Data analysis using Mann-Whitney and Spearman correlation test. The results showed that there was a relationship between PSA levels and IGF1 (p0.05). There was a relationship between PSA and IGF1 (p0.05). There was a relationship between PSA and IGF1 (p0.05).